Inorganic carbon in a high latitude estuary-fjord system in Canada's eastern Arctic. (5th September 2016) - Turk, D.; Bedard, J.M.; Burt, W.J.; Vagle, S.; Thomas, H.; Azetsu-Scott, K.; McGillis, W.R.; Iverson, S.J.; Wallace, D.W.R.
Abstract: Rapidly changing conditions in the Arctic can have a significant impact on biogeochemical cycles and can be particularly important in high latitude estuary-fjord systems with abundant and diverse freshwater sources. This study provides a first look into the inorganic carbon system and its relation to freshwater sources in Cumberland Sound in the east coast of Baffin Island, Nunavut, Canada. These data contribute to the very limited set of inorganic carbon measurements in high latitude estuary-fjord systems. During the ice-free conditions in August 2011, the meteoric freshwater fractions (MW) in the upper 40 m ranged from 11 to 21% and no sea ice melt (SIM) was present in the Sound. Surface waters were undersaturated with pCO2 (260 and 300 μatm), and DIC and TA ranged between 1779 and 1966 μmol DIC kg −1, and 1922 and 2140 μmol TA kg −1, respectively. Aragonite saturation (ΩAr ) state ranged from 1.9 in the surface to 1.4 in the subsurface waters. Data show decreasing TA and ΩAr with increasing MW fraction and suggest that Cumberland Sound waters would become aragonite undersaturated (ΩAr  < 1) at MW = 0.37 (95% CI: 0.29 to 0.56). Estimated local δ 18 O (−19.2‰) and TA (174 μmol TA kg −1 ) end-members indicate MW was most likely a mixture of river water and glacial melt. In August 2012, MW fractions at the surface were between 8 and 11.5%, and SIM between 7 and 23%. Significant interannual variability of summertime SIM could potentially result in ΩAr undersaturation.